(untitled) (Journal of Universal Science Research, 2025)
Setting goals not only for success but only for everything you want to achieve tend to boost your confidence , motivation as well as stimulate person all growth. But, sometimes you can be overwhelmed with negative thinking, if you don’t achieve your goals. And you will realize it is one step to the success year by year.